Social Conflict among Mining Company and Community - Ricardi S Adnan; Gumilar Rusliwa Somantri (Indonesian Journal of Religion and Society, 2022)
Conflicts between communities and mining companies in the district Alpha Sulawesi was a series of problems the last few years. This study found that the problems occurred between the community and mining companies were based on distorted social interactions, namely communication problems that did not work perfectly. By using a mixed method, this study which is included in the action research category found that the problem of perception and interpretation was a dominant factor in causing disputes to tension. Following the framework of Miller & Sinclair (2012), perceptions that arise and develop include physical, economic, environmental, and social issues. Through a quantitative approach with interviews using questionnaires to as many as 260 respondents spread across 13 villages and 3 sub-districts and a qualitative approach through in-depth interviews and group discussions with influential figures in these villages and PTMS management. Using the framework of Resource community member’s perception of coal industry risk and benefit, the results of this study also found differences in viewpoints in viewing environmental aspects of public health and social care.